Da leitura para a escrita do artigo de opinião: uma proposta de intervenção no ensino fundamental - Silva, Edvaldo José da (2015)
This dissertation presents a study on text reading and production of the genre of discourse opinion article. The general objective of this research is evaluate how a proposal of intervention, based on the utilization of a didactic sequence with the genre opinion article, can contribute to the development of students‟ reading and writing competence from a class of 9th Year, of Elementary School (Ensino Fundamental). The didactic sequence with the opinion article, used in the intervention, was proposed by Dolz, Noverraz e Schneuwly (2004) and included the following steps: initial production; seven modules of reading; rewriting; final production. As theoretical base, we adopted the following authors‟ contributions: a) in the work with text reading and production, Kato (1995), Rojo (2009), Soares (2006), Kleiman (2010), Liberato (2012), Cavalcanti (1992); Kleiman (2012); Koch (1989); Leffa (1996); Lopes (1997); Solé (1998), Tomitch (2008), among others; b) in the genre studies: Bakhtin (2003), Marcuschi (2002); c) on approach about the characteristics of opinion article, Coimbra e Chaves (2012), Rodrigues (2005). The methodological procedure adopted was an action research, as proposed by Thiollent (2004) and the corpus is formed by six opinion articles, being five taken from newspapers, one from a magazine and three productions of the genre opinion article performed by students-participants. The conception of reading defended in this research is that understood as an interactional process among the author, the text and the reader. About the text production, we defended that it stems from the work of reading, that perform and comprises the following steps: the preparation, the writing, the evaluation and the rewriting. The opinion article was approached in this work by considering its compositional form, its thematic content, its style and its circulation sphere or domain. The results achieved with this research demonstrated that the targeted goals were achieved, because occurred a notable advance in the quality of students-participants‟ written production, specifically in relation to seizure of constituent elements of the textual genre opinion article.